Characteristics of a first-generation x-ray system - Kemerink, Martijn; Dierichs, Tom J.; Dierichs, Julien; Huynen, Hubert J. M.; Wildberger, Joachim Ernst; Engelshoven, Jos M. A. van; Kemerink, Gerrit J. (Radiology, 2011)
PurposeTo compare the antiquated x-ray system of Hoffmans and van Kleef (circa 1896) with modern x-ray equipment in terms of radiation dose, x-ray beam properties, image quality, and electrical parameters.Materials and MethodsThe antiquated x-ray system consisted of a Ruhmkorff inductor, battery, and Crookes tube. The radiation dose rate, x-ray beam properties, and electrical characteristics of this system were determined. A modern computed radiography plate was used to compare images of a hand specimen obtained by using the antiquated system with images obtained by using the modern system.ResultsA peak voltage of 73 kV was obtained with an 8-V battery. With Crookes tube number 9, the half-value layer of the generated x-rays was 0.56 mm Al. Pinhole images showed that the x-rays originated from an extended area of the glass wall, causing image blurring. When measured on the skin of a hand specimen, the radiation dose of the antiquated system was about 10 times greater than that of the modern system for the same detector signal. The estimated skin dose was about 74 mGy for the antiquated system and 0.05 mGy for the modern system. The corresponding exposure times were 90 minutes and 21 msec.ConclusionRadiation dose and exposure time of the antiquated system were greater than those of the modern system by about three and five orders of magnitude, respectively. Images of the hand specimen obtained with the antiquated system were severely blurred but were still awe inspiring, considering the simplicity of the system.© RSNA, 2011Supplemental material: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.11101899/-/DC1